Fig. 8. Protobranch bivalves from Calcari a in Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Fig. 8. Protobranch bivalves from Calcari a Lucina seep deposits in northern Italy. A–D. The nuculid Nucula aff. sulcata Bronn, 1831. A. MSF 2366. B. Right valve from Le Colline (MSF 1212). C. Right valve from Le Colline (MSF 1210). D. Left valve from Ca' Cavalmagra (MSF 1311). E–F. The solemyid Acharax doderleini (Mayer, 1861) from Ca' Fornace erratics. E. External mold of right valve (MSF 2361). F. Internal mold of right valve (MSF 2360). Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on page 139, DOI:10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702